2018
DOI: 10.31364/scirj/v6.i7.2018.p0718542
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leadership on Employee Performance with Organizational Culture and Work Motivation as Intervening Variables

Abstract: The purpose of this research is testingand analyzing the influence of leadership on employee performance through organizational culture and work motivation. Population and sample consist of State Civil Apparatus in Government of Pasuruan regency at Integrated Service and Investment Service and the Regional Finance Board were 130 respondents. Data analysis method used is path analysis processed with software Smart Partial Least Square (PLS). The result of hypothesis testing found that 1) leadership did not dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
1
Order By: Relevance
“…The results of the study are in line with the findings of Iman & Lestari (2019); Rawashdeh (2018), which show that leadership has a positive effect on employee performance. Fitriasari & Mauludin (2018), found that leadership does not directly affect employee performance, where leadership  Effect of Supervision on Performance From the research results, the value of the Original Sample (O) is positive.…”
Section:  Influence Of Leadership On Performancementioning
confidence: 88%
“…The results of the study are in line with the findings of Iman & Lestari (2019); Rawashdeh (2018), which show that leadership has a positive effect on employee performance. Fitriasari & Mauludin (2018), found that leadership does not directly affect employee performance, where leadership  Effect of Supervision on Performance From the research results, the value of the Original Sample (O) is positive.…”
Section:  Influence Of Leadership On Performancementioning
confidence: 88%
“…Hasil penelitian ini mendukung penelitian terdahulu oleh Jeremy et al (2012); Iman & Lestari (2019); Rawashdeh (2018); dan Fitriasari & Mauludin (2018) yang mengutarakan bahwa faktor kepemimpinan dalam suatu organisasi menjadi sangat penting manakala individu/anggota organisasi memiliki dinamika yang tinggi dalam aktivitasnya. Obiwuru et al (2011) menemukan fakta bahwa gaya kepemimpinan yang berbeda dapat menghasilkan kinerja yang berbeda.…”
Section: Pembahasan Kepemimpinan Militer Dan Kinerjaunclassified
“…Better leadership will produce high jobs so that employee performance will increase. Likewise, on the contrary, poor leadership results in low work motivation so that employee performance will decline (Fitriasari & Mauludin, 2018).…”
Section: The Effect Of Islamic Leadership On Islamic Business Performance Through Islamicmentioning
confidence: 99%